Batch crystallization of rhodopsin for structural dynamics using an X‐ray free‐electron laser. Issue 7 (1st July 2015) - Wu, Wenting; Nogly, Przemyslaw; Rheinberger, Jan; Kick, Leonhard M.; Gati, Cornelius; Nelson, Garrett; Deupi, Xavier; Standfuss, Jörg; Schertler, Gebhard; Panneels, Valérie
<x xml:space="preserve">Abstract</x> Rhodopsin is a membrane protein from the G protein‐coupled receptor family. Together with its ligand retinal, it forms the visual pigment responsible for night vision. In order to perform ultrafast dynamics studies, a time‐resolved serial femtosecond crystallography method is required owing to the nonreversible activation of rhodopsin. In such an approach, microcrystals in suspension are delivered into the X‐ray pulses of an X‐ray free‐electron laser (XFEL) after a precise photoactivation delay. Here, a millilitre batch production of high‐density microcrystals was developed by four methodical conversion steps starting from known vapour‐diffusion crystallization protocols: (i) screening the low‐salt crystallization conditions preferred for serial crystallography by vapour diffusion, (ii) optimization of batch crystallization, (iii) testing the crystal size and quality using second‐harmonic generation (SHG) imaging and X‐ray powder diffraction and (iv) production of millilitres of rhodopsin crystal suspension in batches for serial crystallography tests; these crystals diffracted at an XFEL at the Linac Coherent Light Source using a liquid‐jet setup.